Intravenous thrombolysis in ischemic stroke patients based on non-contrast CT in the extended time-window - Emde, Julia; Baumgart, Romy; Langguth, Niklas; Juenemann, Martin; Gerner, Stefan T. (Frontiers in Stroke, 2022)
Purpose of review Recent trials provided evidence for safety and efficacy of intravenous thrombolytic therapy (IVT) in ischemic stroke patients beyond the 4.5 h time-window if ischemic penumbra is present in multimodal imaging. However, advanced imaging by either Magnet Resonance Imaging (MRI) or Computed Tomography Perfusion (CTP) is not available 24/7 at most stroke-centers. Therefore, the current review addresses the use of non-contrast CT (NCCT) to identify ischemic stroke patients suitable for IVT in the unknown or extended time-window in terms of efficacy and safety. Recent findings The current data on NCCT based IVT strategies in ischemic stroke patients presenting in the unknown or late time-window are relatively scarce and mainly provided by small retrospective samples. One larger registry (TRUST-CT) underlines the safety and efficacy of IVT without advanced imaging with more IVT-patients reaching an excellent outcome compared to the non-IVT treated control group. Current meta-analysis provides evidence that the rate of symptomatic intracerebral hemorrhage (sICH) is similar in the wake-up and unknown onset time-window compared to the 4.5 h time-window if patients are selected by NCCT. Results of the upcoming TWIST-trial investigating Tenecteplase (TNK) for NCCT-based IVT revealed no signals regarding an increased rate of sICH, however there was no benefit regarding functional outcomes. Summary So far, it is not well-established whether advanced imaging is indispensable and NCCT could be sufficient to identify stroke patients in the extended window who would benefit from IVT-treatment. However, current data suggests the safety of NCCT-based IVT in the extended time-window. Therefore, unavailable advanced neuroimaging should not cause delay, or even exclusion of patients from IVT and other recanalizing therapies per se.